1998
DOI: 10.1016/s0266-7681(98)80178-2
|View full text |Cite
|
Sign up to set email alerts
|

Vein Implantation for Treatment of Painful Cutaneous Neuromas

Abstract: Based on the theory that recurrent neuroma formation can be prevented if the cut nerve end is implanted into the lumen of a vein, 14 patients have been treated by neuroma excision followed by proximal vein implantation over the last 5 years. Thirteen patients reported dramatic pain relief following surgery, and this was sustained in all but one case. Both failures were re-explored, when it was found that the nerve had pulled out of the vein, leading to recurrent neuroma formation. Both cases were revised succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…This technique is similar to that described by Herbert and Filan. 10 The problem that the authors encountered was that the nerve may retract and pull out of the vein, leading to failure and potential re-neuroma formation. Thus a dual anchoring technique has been developed to help reduce tension on the nerve and subsequent failure.…”
Section: Technical Notementioning
confidence: 99%
See 1 more Smart Citation
“…This technique is similar to that described by Herbert and Filan. 10 The problem that the authors encountered was that the nerve may retract and pull out of the vein, leading to failure and potential re-neuroma formation. Thus a dual anchoring technique has been developed to help reduce tension on the nerve and subsequent failure.…”
Section: Technical Notementioning
confidence: 99%
“…9 The clinical study involves 14 patients with 79% of patients symptom free and the rest with minor residual symptoms, with a follow-up at 15 months. 10 …”
Section: Introductionmentioning
confidence: 99%
“…7 In this technique, the affected nerve is identified proximal to the neuroma and dissected distally to free the neuroma from surrounding scar tissue, resected back to the healthy nerve, and mobilized sufficiently to allow implantation into an adjacent vein without tension. 7,33 The nerve is then inserted into the vein and held with an epineural suture through the venous wall. 7,33 Results from a study done by Herbert 33 showed that 13 of 14 patients reported dramatic, immediate pain relief, with 86% successful after the initial surgery and 100% successful after revision.…”
Section: Treatment Of Neuromasmentioning
confidence: 99%
“…7,33 The nerve is then inserted into the vein and held with an epineural suture through the venous wall. 7,33 Results from a study done by Herbert 33 showed that 13 of 14 patients reported dramatic, immediate pain relief, with 86% successful after the initial surgery and 100% successful after revision. Herbert also showed histologically that nerve stumps transposed into a vein lumen showed more organized endoneural architecture, small fascicles oriented in the same direction, and a high rate of myelinated axons.…”
Section: Treatment Of Neuromasmentioning
confidence: 99%
“…Among those studies presenting short-term results, there were three on neuroma resection and transposition of the proximal nerve stump into the lumen of a vein [2][3][4]. An experimental study and two of the clinical studies on this technique were published by the author [3][4][5].…”
Section: Introductionmentioning
confidence: 99%